Heat Stroke: A Medical Emergency Appearing in New Regions - Sofie Søndergaard Mørch; Johnny Dohn Holmgren Andersen; Morten Heiberg Bestle (Case Reports in Critical Care)
Heat stroke is an acute, life-threatening emergency characterized clinically by elevated body temperature and central nervous system dysfunction. Early recognition and treatment including aggressive cooling and management of life-threatening systemic complications are essential to reduce morbidity and mortality. This case report describes two Danish patients diagnosed with heat stroke syndrome during a heat wave in the summer of 2014. Both patients were morbidly obese and had several predisposing illnesses. However since heat stroke is a rare condition in areas with temperate climate, they were not diagnosed until several days after admittance; hence treatment with cooling was delayed. Both patients were admitted to the intensive care unit, where they were treated with an external cooling device and received treatment for complications. Both cases ended fatally. As global warming continues, more heat waves will occur in previously cooler regions. Therefore it is important to raise awareness of heat stroke since outcome depends on early recognition and rapid cooling.